Happines of the psychology - Segura Díez, María del Carmen (2009)
Happiness is a so serious and important fact in our life that this wouldn’t be conceived without it. A human life in which happiness doesn’t have any sense of happiness, it wouldn’t be a human life. Throughout this article, we will try to answer to the question: what’s happiness? , clarifying important questions such as: What are positive emotions? or which of them represent welfare sensation? To the end, we will briefly describe the most recent theoretical models in the study field of happiness, and offer the conclusions and proposals about it.